VESTIBULAR FUNCTION IN A GROUP OF ADULTS WITH HIV/AIDS ON HAART - Khoza-Shangase, Katijah (African Journal of Infectious Diseases (AJID), 2017)
Background: The high prevalence of HIV/AIDS and the established otological manifestations of the disease have important implications for research into vestibular function in this population.Materials and Methods: The main aim of the current study was to investigate and monitor the vestibular status in a group of adult patients with AIDS receiving Highly Active Antiretroviral Therapy (HAART) and other therapies in a hospital outpatient clinic in Gauteng, South Africa. The study was exploratory and observational in nature, with repeated measures in the form of pre- and post-treatment survey; and a control group. The measures were taken before commencement of antiretroviral therapy (ARVs), three months after initiation of treatment and six months into therapy. A comparison of results of the control group and treatment group was done for all objectives. A total of 150 (104 in the treatment group and 46 in the control group) participants who were recruited through a nonprobability convenience sampling technique were included in the study. All participants were at stage three of HIV/AIDS according to their CD4+ T-cell counts at baseline. Data were analysed through descriptive statistics.Results: Findings from the current study revealed occurrence of acute vertigo which spontaneously resolved in adults with AIDS on HAART over a monitoring period of six months; with this occurrence being higher in participants on HAART than in the control group. The symptoms occurred after diagnosis with HIV and mostly after HAART initiation; and participants who experienced vertigo did not report this to their attending doctor. Furthermore, there was a lack of a relationship between the increasing occurrences of hearing loss in the group to the presentation of vertigo over the six months of monitoring.Conclusion: Findings from the present study which revealed occurrence of possible acute vertigo that spontaneously resolves in adults with AIDS on HAART, over a monitoring period of six months, add to the existing literature on vestibular function in this population. These findings raise important research as well as clinical assessment and management implications in this population.